The role of community education in training program services for the elderly - Imbar Novansyah; Eko Sulistiono; Nuri David Maria Veronika; Irfan Ardi (Curricula: Journal of Curriculum Development, 2024)
The aging process has significant impacts, including physical changes such as decreased vision and hearing, limited movement, and specific health problems in the elderly. Although aging generally brings physical limitations, it encourages high enthusiasm among elderly learners to participate in training programs. So, this research aims to determine the training program services for the elderly. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation studies. Data were analyzed through reduction, presentation, and conclusion drawing with patterns of data analysis findings. This research involved four informants and one program manager. The results of this study reveal that the program manager provides social support, such as (emotional support, tangible support, informational support, and companionship support) and non-social support through learning software and hardware devices. This contributes to the elderly training program services and the effectiveness, attractiveness, and success of the elderly training program.